Abnormal Pap Smear Results in Outpatient Attendees in a Tertiary Care Center in Kathmandu, Nepal - Khatri, Ratna Adhikari; Budhathoki, Lee; Pande, Arya Rana; Singh, sadikshya (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Cervical cancer is one of the most common cancers in the world. It is the most common cancer among females in Nepal. Progression of pre-invasive precursor lesions called Cervical Intraepithelial Neoplasia (CIN) can result in invasive cancer over years and decades. Papanicolaou smear can detect these lesions early. The aim of this paper is to study the prevalence of abnormal Pap smear test and report the results. Methods: Observational study of Pap smear of 1100 women of age 21 to 65 years attending Gynaecological outpatient department of our hospital over a period of one year. Results: Pap smear results were recorded as per Bethesda system. 35% of smears had epithelial cell abnormality with 62.82% normal smear and 2.13%infections, bacterial vaginosis (1.94%) being most common. The highest epithelial cell abnormality was Low grade squamous intraepithelial lesions (29.90%) followed by Atypical squamous cell of undetermined significance (3.2%). High grade squamous intraepithelial lesions and carcinoma were next to follow (0.97% each). 80% of cancers were Squamous cell carcinoma. Conclusion: Premalignant and malignant lesions were found to be common in cervix. Pap test is simple, quick and effective way of screening them. Screening should be done at least once for all woman after the age of 30 as benefit is maximum in this age group.